Self-repairing cement mortars with microcapsules: A microstructural evaluation approach. (30th January 2020) - Sidiq, Amir; Setunge, Sujeeva; Gravina, Rebecca J.; Giustozzi, Filippo
Highlights: Microstructural analysis of cement mortars was conducted before and after healing. The single-crack geometry and volume was analysed via X-ray tomography. Sphericity, crack width and volume were analysed after a controlled damage. Sodium silica microcapsules healed cracks of up to 203 µm in thickness. Abstract: Cracking is intrinsic in cement-based products, although the cementitious material can potentially self-heal cracks. However, the rate of micro-crack formation is comparably higher than that of the self-healing. Researchers are conducting experiments on self-healing phenomena and have shown that the microencapsulation method is one of the most efficient techniques to transport and mix the healing agent in the cementitious matrix. In this study, sodium silicate is stored inside the polyurethane materials to enhance the self-healing efficiency of the cementitious matrix. Initially, compression and stiffness tests are conducted to assess the recovery of mechanical properties. X-ray tomography images are also reconstructed into three-dimensional sections and self-healing recovery was assessed via porosity content, sphericity, reduction of single crack width and volumetric size. A novel method is used to identify the geometrical definition of the single micro-crack during the self-healing process known as the Structure Model Index. Micro-cracks in mortar samples were developed homogeneously through the entire section of the samples. In this process, it was established that cracks up to 203 µm in thickness were healed.